Diagnosis and treatment of tuberculosis: latest developments and future priorities - Kumar, Kartik; Kon, Onn Min (Annals of Research Hospitals, 2017)
Tuberculosis (TB) continues to impose a significant clinical and socioeconomic burden globally. In 2015, there were 10.4 million new cases of TB and 1.8 million deaths attributable to the disease worldwide. While there has been significant progress in the diagnosis and management of the infection in recent decades, many challenges remain. In addition to addressing the burden of disease caused by drug-sensitive TB, it is important to tackle the increasing threat of multidrug-resistant TB (MDR TB) and latent TB infection (LTBI). Improvements are needed in both diagnostic tools and therapeutic regimens. This article provides an update on the clinical approach to managing drug-sensitive, drug-resistant and latent TB. The global epidemiology of the disease, clinical presentation and approaches to management are discussed. Future research and clinical priorities are considered.